KEPEMIMPINAN TRANSFORMASIONAL SEBAGAI STRATEGI PENGEMBANGAN BUDAYA ORGANISASI DAN KOMPETENSI PEDAGOGIK DI SMP XYZ - Iriani, Everista (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study examines the role of transformational leadership in shaping organizational culture and enhancing pedagogical competence at XYZ Junior High School. Using a case study approach, data were collected through semi-structured interviews, observations, and document analysis involving the principal, vice principal, pedagogical leaders, and teachers. The findings reveal that transformational leadership supports the strengthening of organizational culture through motivation, a shared vision, and an inclusive learning community. However, implementation faces challenges within the four dimensions of transformational leadership: Idealized Influence, Intellectual Stimulation, Individualized Consideration, and Inspirational Motivation. Organizational culture-related challenges include communication across hierarchical levels, aligning leadership practices, and addressing diverse needs and aspirations. Organizational culture plays a crucial role in preparing teachers for change, fostering collaboration, creating a positive work environment, and supporting continuous professional development. This study emphasizes the importance of integrating transformational leadership with a responsive organizational culture to navigate curriculum changes and strengthen pedagogical competence. Keywords: transformational leadership, organizational culture, pedagogical competence